Novinové sloupky Jiřího Hanáka v ćase elektronicke komunikace - Hoffmann, Bohuslav (Stylistyka, 2010)
The paper deals with a well-known genre of joumals and newspapers - the column. The analysis of morę than 100 columns of Jiri Hai k (from the years 2006-2010) resulted in a conclusion that this Czech ioumalist (writing for an independent newspaper Pravo) is a successor of the best representa" ves of Czech democratic joumalism, Kareł Havllćek Borovsk> and Kareł Ćapek. A ffequent topie of a political writer J. Hanak is the conflict bctwcen the European integration and nationalism. His columns and other texts are marked b> a rich vocabulary, numerous metaphors based on an outstanding knowledge of history, by a sarcastic irony and extraordinary elaborated intertextual dimension.